(3TQM ThGgO cJGH GdLeds - (3YHO Gddg Hf eMeO Hf GdSjO GdHWdjhSj, GHf GdSjO GdHWdjhSj, CHh eMeO J (B521 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi YdefG eGde fcf fYde CQOJ Cf CJHY Pdc GdcdGe ai EYQGH EKHGJg heYGfjgG s
(3BNQgG (B:s
(3jfJgi CKfGA bhdg hCfTO ai BNQ GdcJGH (B: (3aeG SHb GdbjSi ef ShA SjQI hdcf WaJ YdeGA ZRdI NGdO s
(3GdfSNI HgG MhGTs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3ef GdNRGfI GdYGeI HeOjfI GdQHGW (B(1701) s
Keywords: (3GdfMhs